„Give God Czechs fortune!“ Czech Nationalism in Brewing - Grisa, Jan (KVASNY PRUMYSL, 2017)
The study deals with the nationalism in brewing at the end of the 19th and the begining of the 20th centuries. The main focus lies on breweries foundation made by national impulse and on the connection between these breweries and another elements of Czech national life. Some specifics of these companies are mentioned too. For example personnel structure, trade policy etc. A part of the study deals with nationalistically tinged brewing periodicals and attention is also paid to antisemitism in brewing.